Zinc coordination is essential for the function and activity of the type II secretion ATPase EpsE. Issue 5 (10th May 2016) - Rule, Chelsea S.; Patrick, Marcella; Camberg, Jodi L.; Maricic, Natalie; Hol, Wim G.; Sandkvist, Maria
Abstract: The type II secretion system Eps in Vibrio cholerae promotes the extracellular transport of cholera toxin and several hydrolytic enzymes and is a major virulence system in many Gram‐negative pathogens which is structurally related to the type IV pilus system. The cytoplasmic ATPase EpsE provides the energy for exoprotein secretion through ATP hydrolysis. EpsE contains a unique metal‐binding domain that coordinates zinc through a tetracysteine motif (CXXCX29 CXXC), which is also present in type IV pilus assembly but not retraction ATPases. Deletion of the entire domain or substitution of any of the cysteine residues that coordinate zinc completely abrogates secretion in an EpsE‐deficient strain and has a dominant negative effect on secretion in the presence of wild‐type EpsE. Consistent with the in vivo data, chemical depletion of zinc from purified EpsE hexamers results in loss of in vitro ATPase activity. In contrast, exchanging the residues between the two dicysteines with those from the homologous ATPase XcpR from Pseudomonas aeruginosa does not have a significant impact on EpsE. These results indicate that, although the individual residues in the metal‐binding domain are generally interchangeable, zinc coordination is essential for the activity and function of EpsE. Abstract : Type II secretion ATPases contain a unique zinc‐binding domain which is absent from homologous type IV pilus retraction ATPases and type IV secretion ATPases. Removal of the entire zinc‐binding domain or disruption of zinc coordination in the type II secretion ATPase EpsE abrogates secretion and prevents ATP hydrolysis, indicating that zinc coordination is essential for the function and activity of type II secretion ATPases.